Practices of personal adornment in neolithic Greece = Praktikes Prosopikes Kosmeses ste Neolithike Ellada - Ifantidis, Fotis (Archaeopress open access, 2019)
The objective of this book is the reconsideration of the practices of personal adornment during the Neolithic period in through the assemblage, extensive bibliographic documentation, and critical evaluation of all the available data deriving from more than a hundred sites in the mainland and the Aegean islands -an archaeological archive of wide geographical and chronological scope. In addition, a thorough study of the personal ornament corpus from the Middle-Late Neolithic Dispilio in Kastoria, an important lakeside settlement in north-western Greece, was conducted. The book begins with an overview of the anthropological and archaeological literature on theoretical and methodological issues concerning practices of personal adornment. Then follows an examination of the problems and key points of study regarding personal adornment in Neolithic Greece, as well as a critical evaluation of the methodological approaches and classification schemes that have been applied in previous archaeological works. Subsequently, the technologies and processes of production, consumption, recycling, deposition, and distribution of personal ornaments in Neolithic Greece are discussed. Finally, the social correlates of personal adornment are explored, as they are reflected in the choice of different raw materials (shell, clay, bone, stone, and metal) and ornament types (beads, pendants, annulets, and so forth).